2003
DOI: 10.1046/j.1523-1747.2003.12406.x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Alterations in Blastic Natural Killer/Extranodal Natural Killer-Like T Cell Lymphoma with Cutaneous Involvement

Abstract: Natural killer and natural killer-like T cell lymphomas represent a rare type of non-Hodgkin's lymphoma originally described to involve the upper aerodigestive tract. This malignancy has been increasingly observed in other extranodal sites, particularly in the skin. Patients with cutaneous natural killer cell lymphoma generally have a poor prognosis; however, the etiology and the underlying molecular pathogenesis remain unclear. This study aimed to investigate comprehensively genomic changes in blastic natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 91 publications
(134 reference statements)
3
16
0
Order By: Relevance
“…This technique has previously been shown to provide accurate analysis of gene copy number alteration in human tumors. 14,15 The value of 2.63 (Po0.001) for the ABL gene was significantly higher than copy number gains for other genes represented in this array. Thus, these data confirm that the high number of FISH signals observed represents amplification of the ABL gene.…”
Section: To the Editormentioning
confidence: 73%
“…This technique has previously been shown to provide accurate analysis of gene copy number alteration in human tumors. 14,15 The value of 2.63 (Po0.001) for the ABL gene was significantly higher than copy number gains for other genes represented in this array. Thus, these data confirm that the high number of FISH signals observed represents amplification of the ABL gene.…”
Section: To the Editormentioning
confidence: 73%
“…Using low-resolution comparative genomic hybridization (CGH), recurrent chromosomal abnormalities have been detected in 70% of cases, while fluorescent in situ hybridization studies demonstrated translocations involving chromosome 5q and 6q. 3,[7][8][9] Similar studies on c-AML are completely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…5A). As QPCR analysis clearly positioned the FGFR1 gene outside of the telomeric boundary of this MCR, and previous studies have implicated FGFR1 as the prime target of 8p amplicon in other cancer types (Simon et al 2001;Edwards et al 2003;Mao et al 2003), interphase FISH was used to verify the amplicon boundaries in several informative samples. Consistent with QPCR data, FISH with a BAC outside of the MCR and including FGFR1 on PT3 revealed only two copies (Fig.…”
Section: Cross Tumor Type Genomic Comparisonsmentioning
confidence: 86%
“…Although novel for NSCLC, the amplicon on chromosome 8p has been observed in several other cancer types, including breast, prostate, bladder carcinomas, and T-cell lymphomas (Dib et al 1995;Simon et al 2001;Edwards et al 2003;Mao et al 2003;Ray et al 2004). Although FGFR1 resides within this larger CNA and has been considered the prime candidate target of this amplification, detailed QPCR and FISH mapping performed in this study defined both boundaries and narrowed the minimal common region that excludes the FGFR1 gene.…”
Section: Discussionmentioning
confidence: 99%